2021
DOI: 10.1186/s13567-020-00868-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody Nb6 fused with porcine IgG Fc as the delivering tag to inhibit porcine reproductive and respiratory syndrome virus replication in porcine alveolar macrophages

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is a highly contagious virus that has led to enormous economic loss worldwide because of ineffective prevention and treatment. In view of their minimized size, high target specificity and affinity, nanobodies have been extensively investigated as diagnostic tools and treatments of many diseases. Previously, a PRRSV Nsp9-specific nanobody (Nb6) was identified as a PRRSV replication inhibitor. When it was fused with cell-penetrating peptide (CPP) TAT, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Mouse anti-PRRSV N and GP5 antibodies were kept in our laboratory ( 71 ). The PRRSV Nsp9 nanobody containing porcine IgG Fc (Nb6-pFc) was kindly provided by Qin Zhao from Northwest A&F University ( 72 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse anti-PRRSV N and GP5 antibodies were kept in our laboratory ( 71 ). The PRRSV Nsp9 nanobody containing porcine IgG Fc (Nb6-pFc) was kindly provided by Qin Zhao from Northwest A&F University ( 72 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 551 to 600 aa in nsp9 were found to play important roles in the stimulation of IL-13 production by reducing m 6 A demethylase FTO expression. Recent studies have shown that amino acids at positions 519, 544, 586, 588, 590, 592, 611, and 643 in nsp9 regulated the high virulence of PRRSV, interacted with other viral proteins, enhanced pathogenicity, and controlled cellular immune response ( 65 , 71 , 72 , 73 ). The amino acid mutations at positions 519 and 544 of PRRSV nsp9 were found to be necessary for the rescue of PRRSV and critical to the replication efficiency of HP-PRRSV, contributing to enhanced pathogenicity ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acids at positions 586 and 592 in nsp9 have been reported to contribute to the replication efficiency of the Chinese HP-PRRSV in PAMs and act as critical sites determining the viral virulence in piglets ( 71 ). The amino acid residues at positions 588, 590, and 643 in nsp9 and at positions 62, 105, and 107 in nanobodies 6 (nb6) have been observed to be involved in nsp9–nb6 interaction, contributing to the inhibition of PRRSV replication ( 72 ). The E608 and E611 aa in nsp9 and Q85 aa in the N protein have been noted to be the pivotal residues involved in the N–nsp9 interaction, acting as anti-attenuation factors for the continuous elongation of nascent transcript during negative-strand RNA synthesis ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Nbs can inhibit virus replication ( 36 38 ). E2 is the most immunogenic protein of CSFV and can produce clinical protective antibodies against CSFV challenge ( 1 ).…”
Section: Discussionmentioning
confidence: 99%